Structure-guided optimization of quinoline inhibitors of Plasmodium N-myristoyltransferase12. Issue 1 (18th November 2016) - Goncalves, Victor; Brannigan, James A.; Laporte, Alice; Bell, Andrew S.; Roberts, Shirley M.; Wilkinson, Anthony J.; Leatherbarrow, Robin J.; Tate, Edward W.
Abstract : Quinolines with balanced activities against both Plasmodium vivax and Plasmodium falciparum N -myristoyltransferase were identified. Abstract : The parasite Plasmodium vivax is the most widely distributed cause of recurring malaria. N -Myristoyltransferase (NMT), an enzyme that catalyses the covalent attachment of myristate to the N-terminal glycine of substrate proteins, has been described as a potential target for the treatment of this disease. Herein, we report the synthesis and the structure-guided optimization of a series of quinolines with balanced activity against both Plasmodium vivax and Plasmodium falciparum N -myristoyltransferase (NMT).